Pengaruh Penggunaan Lensa Kontak Lunak Terhadap Kesehatan Mata Di Optik Padang - Yusfita , Ermi (CV. ITTC INDONESIA, 2024)
The research results showed that respondents did not fully know the correct and correct procedure for using soft contact lenses, this can be seen from 28 respondents (62.2%) knowing the correct procedure for using soft contact lenses and 17 respondents (37.8%) not knowing the procedure for using lenses correct soft contact lenses, 26 respondents (57.8%) understand the impact of using soft contact lenses and 19 respondents (42.2%) do not understand the impact of using soft contact lenses, 29 respondents (64.4%) know about how to overcome the impact of using soft contact lenses. not in accordance with standards and as many as 16 respondents (35.6%) did not know about how to overcome the impact of using soft contact lenses that do not comply with standards,